Downregulation of common cytokine receptor γ chain inhibits inflammatory responses in macrophages stimulated with Riemerella anatipestifer. (April 2018) - Afrin, Fahmida; Fernandez, Cherry P.; Flores, Rochelle A.; Kim, Woo H.; Jeong, Jipseol; Chang, Hong H.; Kim, Suk; Lillehoj, Hyun S.; Min, Wongi
Abstract: Th17-cell-mediated inflammation is affected by the soluble form of common cytokine receptor γ chain (γc ). We previously suggested that inflammatory cytokines including interleukin (IL)-17A are associated with Riemerella anatipestifer infection, which a harmful bacterial pathogen in ducks. Here, the expression profiles of membrane-associated γc (duγc -a) and soluble γc (duγc -b) in R. anatipestifer- stimulated splenic lymphocytes and macrophages, and in the spleens and livers of R. anatipestifer -infected ducks, were investigated. In vitro and in vivo results indicated that the expression levels of both forms of γc were increased, showing that marked increases were detected in the expression of the duγc -b form rather than the duγc -a form. Treatment with γc -specific siRNA downregulated mRNA expression of Th17-related cytokines, including IL-17A and IL-17F, in duck splenic macrophages stimulated with R. anatipestifer, whereas the expressions of interferon (IFN)-γ and IL-2 were enhanced. The results showed that the upregulation of γc, especially the duγc -b form, was associated with expression of Th17-related cytokines during R. anatipestifer infection. Highlights: Th17-mediated inflammation is affected by soluble common cytokine receptor γ chain (γc ). Expression of membrane and soluble γc increased in R. anatipestifer- infected ducks and stimulated lymphoid cells, especially marked expression of the soluble form. γc -specific siRNA downregulated mRNA expression of Th17-related cytokines IL-17A and IL-17F in R. anatipestifer -stimulated macrophages. Upregulation of γc, especially duγc -b (soluble) form, was associated with the expression of Th17-related cytokines during R. anatipestifer infection.